Integrating Land-Use and Food Planning for the Re-territorialisation of Agricultural Activities: A Review of the Literature - Liu, Tianzhu; Melot, Romain; Wallet, Frédéric; Perrin, Coline (The International Journal of Sociology of Agriculture and Food, 2025)
The re-territorialisation of agricultural activities (RAA) refers to the promotion of local food production and its diversification geared towards local consumption. RAA helps to shape the local food system, a subject that is increasingly studied with regard to planning. Land-use and food planning are two local policy areas associated with RAA, yet the way in which they interact to facilitate RAA remains unclear. This research aims to provide a comprehensive understanding of the integration between land-use and food planning by reviewing the scientific literature in these planning fields in the Global North over the past 24 years. We reviewed 161 publications pertaining to RAA-related interests and instruments, intersecting action fields and governance mechanisms. The literature shows the complementarity between land-use and food planning in areas related to RAA, and the consequent need to develop coherent planning strategies to improve the effective implementation of RAA. Land-use planning has a spatial dimension with regulatory instruments, whereas food planning often has a food system and life cycle dimension with strategic instruments. Access to land, collective food infrastructures, and farming practices are three areas around which land-use and food planning can have synergies. Coherence and synergy can also be favoured by a well-established co-governance model, which implies collaboration between sectors, multi-level governmental actors, and a combination of top-down and bottom-up processes. We conclude with suggestions for planning practitioners and provide a future research agenda by appealing for more empirical studies on the intersectional fields of land-use and food planning.